2023
DOI: 10.1093/oncolo/oyad213
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Ejection Fraction in Patients With Ovarian Cancer Treated With Avelumab, Pegylated Liposomal Doxorubicin, or Both

Marc P Bonaca,
Javid J Moslehi,
Jonathan A Ledermann
et al.

Abstract: In the phase III JAVELIN Ovarian 200 trial, 566 patients with platinum-resistant/refractory ovarian cancer were randomized 1:1:1 to receive avelumab alone, avelumab plus pegylated liposomal doxorubicin (PLD), or PLD alone. Cardiac monitoring was included for all patients. We report left ventricular ejection fraction (LVEF) data from the trial. Grade ≥3 cardiac adverse events (AEs) occurred in 4 (2.1%), 1 (0.5%), and 0 patients in the avelumab, combination, and PLD arms, respectively. LVEF decreases of ≥10% to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…The FDA-approved thermosensitive hydrogels based on PLGA copolymers have been widely utilized to deliver therapeutic or bioactive drugs and have broad prospects. The accumulation of metabolites derived from PLGA may elicit inflammatory response and expedite OA progression . However, certain studies did not observe a substantial inflammatory response induced by PLGA; thus, we believed that the local proinflammatory effects were weak and acceptable, which was confirmed in vivo and in vitro Moreover, PEG has been widely used in clinical trials and confirmed its safety in vivo . In vivo clinical trials of PLGA–PEG-PLGA are expected to fully confirm its safety and highlight the feasibility of widespread clinical application. Ex modAtf5 can be conveniently and evenly distributed in aqueous polymer solutions at RT.…”
Section: Discussionmentioning
confidence: 64%
“…The FDA-approved thermosensitive hydrogels based on PLGA copolymers have been widely utilized to deliver therapeutic or bioactive drugs and have broad prospects. The accumulation of metabolites derived from PLGA may elicit inflammatory response and expedite OA progression . However, certain studies did not observe a substantial inflammatory response induced by PLGA; thus, we believed that the local proinflammatory effects were weak and acceptable, which was confirmed in vivo and in vitro Moreover, PEG has been widely used in clinical trials and confirmed its safety in vivo . In vivo clinical trials of PLGA–PEG-PLGA are expected to fully confirm its safety and highlight the feasibility of widespread clinical application. Ex modAtf5 can be conveniently and evenly distributed in aqueous polymer solutions at RT.…”
Section: Discussionmentioning
confidence: 64%